1987
DOI: 10.1590/s0034-89101987000400006
|View full text |Cite
|
Sign up to set email alerts
|

Detecção e tratamento de pacientes amblíopes na cidade de São Paulo, SP (Brasil)

Abstract: e tratamento de pacientes amblíopes na cidade de São Paulo, SP (Brasil). Rev. Saúde públ., S. Paulo, 21:326-30, 1987. RESUMO: Foram estudados retrospectivamente cem pacientes amblíopes de uma clínica particular na cidade de São Paulo, SP, Brasil, escolhidos aleatoriamente, com idades variando de 3 a 48 anos. Foram pesquisados: idade de detecção, meio de detecção, idade de início do tratamento e regularidade do retorno ao consultório. A maior parte dos casos (65%) foi detectada antes dos 7 anos de idade e de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
11

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 2 publications
(1 reference statement)
0
2
0
11
Order By: Relevance
“…Macchiaverni et al (9) , studying 564 school children of Paulínia, Brazil, found that amblyopia was primarily associated with anisometropia in 61.9% of the cases and with strabismus in 28.57%. Early detection of amblyopia and other visual disturbances in children up to 4 years constitutes a valuable preventive measure (14,(42)(43)(44)(45) . There is no doubt that results of visual recovery are more rewarding when the problem is detected and treated in younger children.…”
Section: Discussionmentioning
confidence: 99%
“…Macchiaverni et al (9) , studying 564 school children of Paulínia, Brazil, found that amblyopia was primarily associated with anisometropia in 61.9% of the cases and with strabismus in 28.57%. Early detection of amblyopia and other visual disturbances in children up to 4 years constitutes a valuable preventive measure (14,(42)(43)(44)(45) . There is no doubt that results of visual recovery are more rewarding when the problem is detected and treated in younger children.…”
Section: Discussionmentioning
confidence: 99%
“…In Israel and Sweden, screening to detect amblyopia is performed for school-age children. Ethical concerns have been raised regarding this screening, however, as the results may subject children to bullying, with an adverse impact on their mental health (38) . Researchers emphasize the importance of trying to discover the age of onset of abnormal visual experience, as this information is believed to be essential for choosing specific treatment, at least during each of the two sensitive periods of human visual development (17) ( Table 1).…”
Section: Diagnosismentioning
confidence: 99%
“…promoção da saúde ocular é um princípio bási-co de incremento na qualidade de vida, pois uma melhor capacidade visual permite o desenvolvimento de potencialidades, a melhora no rendimento escolar e a participação plena na sociedade (1)(2)(3)(4)(5)(6)(7)(8)(9) . Segundo estimativa da Organização Mundial de Saúde (OMS) para o ano de 2002 (10) , há quase 36,9 milhões de cegos no mundo.…”
unclassified
“…No Brasil, existem 98 milhões de pessoas com algum tipo de deficiência visual, dos quais 80 milhões não têm acesso a qualquer tratamento (11)(12) . Observou-se que a ambliopia, a baixa visual uni ou bilateral sem nenhum substrato orgânico detectável pelo exame oftalmológico, é uma das maiores causas de cegueira prevenível principalmente em crianças (4,(6)(7)(8)(9) . A preocupação em detectar e tratar precocemente problemas oculares que levam a ambliopia em crianças incentivou a criação, em várias partes do mundo, de programas de triagem visual, desde o ingresso da criança na escola, para avaliação por oftalmologistas (2,4,6,(8)(9)13) .…”
unclassified
See 1 more Smart Citation